Re-examination of the distribution and species diversity of the genus Padina (Dictyotales, Phaeophyceae) in the Mediterranean Sea - Pagana, Ilaria; Marroccia, Genny; Marletta, Giuliana; Alongi, Giuseppina (Phytotaxa, 2023)
This study aimed to expand knowledge on the distribution and biodiversity of the genus Padina in Sicily and in the Mediterranean Sea. Thanks to the studies of samples collected along the Sicilian coast and the re-examination of herbarium specimens labelled as Padina pavonica, we reported the following five species in Sicily: P. ditristromatica, P. gymnospora, P. pavonica, P. pavonicoides and P. tetrastromatica. Particularly, we documented the first supported occurrence of P. gymnospora in the Mediterranean Sea and the first finding of P. pavonicoides and P. tetrastromatica along the Italian coast. Furthermore, a new key was created for the identification of all species belonging to the genus Padina present in the Mediterranean Sea today.